EXPLORING THE CORRELATION BETWEEN LUTEINIZING HORMONE AND PROLACTIN LEVELS IN WOMEN WITH COVID-19-INDUCED MENSTRUAL ABNORMALITIES - Najmutdinova, D.K.; Yunusova, D.X. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. The COVID pandemic has underscored the virus's impact on various bodily systems, including the reproductive system. This study aims to explore the relationship between Luteinizing Hormone (LH) and Prolactin levels in females who have recovered from COVID-19 and are experiencing menstrual abnormalities. Material and methods. This was a comprehensive, retrospective cohort study involving 150 women of reproductive age who reported menstrual abnormalities after recovering from COVID-19. They were divided into two groups for comparative analysis: the COVID-19 group, comprising women with confirmed cases of the disease, and the control group, consisting of women with menstrual irregularities unrelated to COVID-19. Results. We identified a correlation of clinical manifestations between the level of LH and prolactin in the group of patients who had suffered COVID-19; they identified a significantly significant, moderately strong negative correlation relationship (r=-0.7813 P<0.001), which shows that the decrease in LH in patients who had suffered COVID 19 is still one of the biggest causes of menstrual irregularities. The study further delves into how these hormonal imbalances correlate with the type and severity of menstrual abnormalities reported. Conclusion. The observed hormonal imbalances, characterized by elevated Prolactin and reduced LH levels, suggest a significant disruption of the HPO axis, likely mediated by the stress and inflammatory responses elicited by COVID-19. These findings highlight the intricate relationship between infectious diseases and hormonal regulation, underscoring the necessity for healthcare providers to be vigilant of reproductive health concerns in women recovering from COVID-19.